Trimetazidine Attenuates Exhaustive Exercise-Induced Myocardial Injury in Rats via Regulation of the Nrf2/NF-κB Signaling Pathway - Zhang, Hongming; Liu, Moyan; Zhang, Yuyan; Li, Xiaoyan (Frontiers in Pharmacology, 2019)
Exhausted exercise has been reported to cause the damage of myocardial structure and function in terms of cardiomyocyte apoptosis, oxidative stress and energy metabolism disturbance. Trimetazidine (TMZ), as an anti-ischemic agent, has been approved to be effective in promoting myocardial energy metabolism, anti-inflammatory and anti-oxidation. However, few studies exam the effects of TMZ on myocardial injury induced by exhausted exercise. To investigate whether TMZ could ameliorate the exhaustive exercise-induced myocardial injury and explore the underlying mechanisms, here the rat model of exhaustive exercise was induced by prolonged swimming exercise and early administration of TMZ was performed on rats before any exercise. In the present study, we demonstrated cardiomyocyte damage in exhaustive exercised rats along with elevations in cTnI and NT-proBNP, and reduced CX43 expression level. The early administration of TMZ was found to modulate oxidative stress by increasing GSH, SOD and GSH-Px activities, and decreasing MDA activity. Additionally, the results showed reduced Bax/Bcl-2 ratio and up-regulated cleaved caspase-3, cleaved PARP and cytochrome c levels in the myocardium of rats treated with TMZ, indicating that TMZ might meliorate myocardial injury by inhibiting apoptosis. Furthermore, we found that TMZ was able to regulate oxidative stress and cardiomyocyte apoptosis via inhibition of NF-κB and activation of Nrf2/HO-1 signaling pathways. Therefore, we suggested that TMZ might be effective in cardioprotection, which provides an insight of the treatment to exhaustive exercise-induced myocardial injury.